2009
DOI: 10.1016/j.physleta.2009.03.039
|View full text |Cite
|
Sign up to set email alerts
|

A supersymmetric Sawada–Kotera equation

Abstract: A new supersymmetric equation is proposed for the Sawada-Kotera equation. The integrability of this equation is shown by the existence of Lax representation and infinite conserved quantities and a recursion operator.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 19 publications
0
43
0
Order By: Relevance
“…A number of supersymmetric extensions have been formulated for both classical and quantum mechanical systems. In particular, such supersymmetric generalizations have been constructed for hydrodynamic-type systems (e.g., the Korteweg-de Vries equation [2,3], the Sawada-Kotera equation [4], polytropic gas dynamics [5,6] and a Gaussian irrotational compressible fluid [7]) as well as other nonlinear wave equations, e.g., the Schrödinger equation [8] and the sine/sinh-Gordon equation [9][10][11]. Parameterizations of strings and Nambu-Goto membranes have been used to supersymmetrize the Chaplygin gas in (1 + 1) and (2 + 1) dimensions respectively [12].…”
Section: Introductionmentioning
confidence: 99%
“…A number of supersymmetric extensions have been formulated for both classical and quantum mechanical systems. In particular, such supersymmetric generalizations have been constructed for hydrodynamic-type systems (e.g., the Korteweg-de Vries equation [2,3], the Sawada-Kotera equation [4], polytropic gas dynamics [5,6] and a Gaussian irrotational compressible fluid [7]) as well as other nonlinear wave equations, e.g., the Schrödinger equation [8] and the sine/sinh-Gordon equation [9][10][11]. Parameterizations of strings and Nambu-Goto membranes have been used to supersymmetrize the Chaplygin gas in (1 + 1) and (2 + 1) dimensions respectively [12].…”
Section: Introductionmentioning
confidence: 99%
“…A number of supersoliton and multi-supersoliton solutions were determined by a Crum-type transformation [19], [21], [25] and it was found that there exist infinitely many local conserved quantities. A connection was established between the super-Darboux transformations and super-Bäcklund transformations which allow for the construction of supersoliton solutions [11], [13], [16], [17], [20], [22], [24].…”
Section: Introductionmentioning
confidence: 99%
“… Supersymmetric Sawada–Kotera equation (λ=32) normalΦt=normalΦ5+5normalΦ3false(scriptDnormalΦfalse)+5normalΦ2false(scriptDΦ1false)+5normalΦ1(DΦ)2and in components it is of the form {vt=v5+5v3v+5v2v1+5v1v25ξ3ξ1ξt=ξ5+5ξ3v+5ξ2v1+5ξ1v2.The recursion operator of the supersymmetric Sawada–Kotera equation was deduced from its Lax equation , and later factorized by Popowicz into two “odd” Hamiltonian operators, which allow us to rewrite the recursion operator in a neater form as truerightleft=right()x2D+2Φx+2xΦ+DΦDx1false(x2scriptD+2normalΦx2em2emright+0.16em2xnormalΦ+scriptDnormalΦscriptDfalse)scriptD1false(xscriptD+normalΦfalse)2scriptD1. …”
Section: A Complete List Of Scalar λ‐Homogeneous (λ>0) N=1 Supersymmementioning
confidence: 99%
“…Supersymmetric Sawada–Kotera equation (λ=32) normalΦt=normalΦ5+5normalΦ3false(scriptDnormalΦfalse)+5normalΦ2false(scriptDΦ1false)+5normalΦ1(DΦ)2and in components it is of the form {vt=v5+5v3v+5v2v1+5v1v25ξ3ξ1ξt=ξ5+5ξ3v+5ξ2v1+5ξ1v2.…”
Section: A Complete List Of Scalar λ‐Homogeneous (λ>0) N=1 Supersymmementioning
confidence: 99%